2014
DOI: 10.1097/meg.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Management of bleeding gastric varices

Abstract: A single session of histoacryl sclerotherapy is effective in the majority of patients with active gastric variceal bleeding. Rebleeding was observed in one-fourth of patients, half of whom were controlled successfully by repeated histoacryl sclerotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A single session of GV sclerotherapy (GVS) seems to be effective for the majority of patients with active GV bleeding. [ 17 ] One interesting finding of our study was the high frequency of second-look endoscopy. Although the hemostasis control rate was high (262/311, 84.2%), and only a few patients required a second procedure (12/311, 7%), one-fourth of patients had to undergo second-look endoscopy.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A single session of GV sclerotherapy (GVS) seems to be effective for the majority of patients with active GV bleeding. [ 17 ] One interesting finding of our study was the high frequency of second-look endoscopy. Although the hemostasis control rate was high (262/311, 84.2%), and only a few patients required a second procedure (12/311, 7%), one-fourth of patients had to undergo second-look endoscopy.…”
Section: Discussionmentioning
confidence: 83%
“…Tissue adhesives including cyanoacrylate-based compounds have been used successfully for the treatment of GVs. [ 3 17 18 19 ] The initial hemostasis control rate for GV bleeding is >90%, and the rebleeding rate is around 22%-37%. [ 20 21 22 23 ] Following GVS, the average mortality rate of GV bleeding is approximately 10%-30%.…”
Section: Discussionmentioning
confidence: 99%
“…NBCA was injected during endoscopy in 42 studies [ 10 , 11 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 61 ] and through a direct percutaneous approach for stomal varices in 1 study [ 60 ]. The types of NBCA glue used in the included studies were as follows: Histoacryl ® (B. Braun, Melsungen, Germany) was the most used NBCA glue (37 studies, 3282 patients, 94.2% of patients) [ 10 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ,…”
Section: Resultsmentioning
confidence: 99%
“…The most used NBCA-Lipiodol ® mixture ratio was 1:1 in 25 studies involving 2208 patients [ 10 , 21 , 22 , 23 , 24 , 27 , 30 , 31 , 32 , 33 , 35 , 36 , 38 , 41 , 43 , 48 , 50 , 51 , 52 , 53 , 57 , 58 , 59 , 61 ]. Other ratios were 1:1.4 in 4 studies (266 patients) [ 25 , 37 , 45 , 54 ], 1:1.6 in 7 studies (391 patients) [ 11 , 26 , 28 , 29 , 39 , 49 , 56 ], 1:1.8 in 2 studies (54 patients) [ 29 , 60 ], 1:1 or 1:1.6 in 1 study (21 patients) [ 47 ], 1:3 in 1 study (37 patients) [ 40 ], 2:1 in 1 study (97 patients) [ 34 ], and 2.3:1 in 1 study (17 patients) [ 46 ]. In 1 study, the ratio range was 1:1 to 1:1.5 (97 patients) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…One-session PARTO procedure was sufficient for treating both hemostasis and obliteration of GV in our 2 patients. A previous study indicated that 25% of patients experience re-bleeding after histoacryl sclerotherapy of active gastric variceal hemorrhage ( 27 ). Therefore, PARTO could be an alternative method for preventing recurrent hemorrhage in patients with active gastric variceal bleeding.…”
Section: Discussionmentioning
confidence: 99%